The participation of the leading parties of Kazakhstan and China in the country's modernization (Journal of Oriental Studies, 2016)
the article considers a question of the role of the dominating party of Kazakhstan and ruling party of China in the country’s modernization. Compares the similarities and differences between the People's Democratic Party “Nur otan” and the Communist Party of China. it is discussed the policy of carrying out of modernization, the main actions of political parties of both countries with a view of modernization implementation.
Keywords: reform; development; leading party